Body-worn cameras and arrest: Zooming in on disaggregated metrics and possible unintended consequences. (July 2021) - McCarty, William P.; Meng, Zhe; Buslik, Marc S.; Moreno, Rafael
Abstract: Purpose: This study sought to assess the effects of body-worn cameras (BWCs) on arrest in the Chicago Police Department (CPD). It builds on the small number of studies that have explored the BWC-arrest nexus through its focus on outcome measures disaggregated by initial arrest category to see if there is additional specificity to the relationship. Methods: This study uses a quasi-experimental design and propensity score matching (PSM) to compare similar groups of spatial units — police patrol districts – in the CPD over a 30-month study period. It also uses multivariate methods to assess whether difference scores in various types of arrest changed significantly over time after the introduction of BWCs. Results: The results showed that in the BWC districts, arrests for misdemeanor marijuana possession increased as time increased (i.e. the difference scores became less negative). This tendency did not appear in a control group of districts. For all other categories of arrest, change occurred at similar rates in the BWC- and control-districts. Conclusion: An upward trend over time in arrests for marijuana possession after the introduction of BWCs could be an unintended consequence that may undermine benefits a department and community may gain from reductions in use of force and complaints. Highlights: Study examines the effects of body-worn cameras on arrest in a large police agency. Study matches police districts and analyzes numerous categories of arrest. Results indicate body-worn cameras increase misdemeanor marijuana arrests. Study discusses potential unintended consequences of body-worn camera technology.